Use of immuno-dominant epitope derived from genotype 4 as a diagnostic reagent for detecting the antibodies against Hepatitis E Virus - Bing-shui, Xiu (BioMed Central, 2013)
BACKGROUND: Despite the genotype 4 has become the dominant cause of hepatitis E disease in China, none antigen derived from genotype 4 of hepatitis E virus (HEV) was used in current commercial anti-HEV immunoassay, and the serological reactivity of antigen derive from genotype 4 is not well-charactered. METHODS: We expressed and purified the 4 main immuno-dominant epitopes derived from genotype 1 and 4 including ORF2 (410-621aa) of genotype 4, ORF3 (47-114aa) of genotype 4, ORF2 (396-606aa) of genotype 1 and ORF3 (56-123aa) of genotype 4. RESULTS: The ORF2 of genotype 4 displayed good diagnostics performance according to ROC analysis using in-house panel, and the immunoassays based the ORF2 of genotype 4 was then developed to detect the anti-HEV IgG antibodies and evaluated further in 530 anti-HEV IgG positive specimens and 380 negative specimens. The sensitivity and the specificity is 98.1% (520/530) and 94.7% (360/380) for immunoassay based on ORF2 of genotype 4, 96.6% (512/530) and 92.6% (352/380) for commercial immunoassay based on genotype 1. It is noted that all of the positive samples will be detected by combing two assays together. The anti-HEV immunoassays based on genotype 4 are in accordance with Chinese anti-HEV national standard,and show an good agreement of 95.8% with commercial assay (kappa=0.913, P=0.014). CONCLUSIONS: The immunoassay based on ORF2G4 displays good performance, and combining assay based on genotype 1 together with genotype 4 will benefit the HEV diagnosis in large scale samples.